Problemática jurídica del desahucio como forma de terminación del contrato de trabajo y las bonificaciones por parte del empleador. - Andrade Dávila, Oscar Rubén (2015)
The legal issues regarding this investigation is aimed at legal analysis of the labor regime in Ecuador, as it pertains to a legal institution of singular importance and significance within the employer-employee relationship as indeed it is the eviction and bonus scheme . The Constitution of the Republic of Ecuador, in Article 33 recognizes the work as a right and a social duty, a source of personal fulfillment and economic base. From this point of view, it is important to note that the work constitutes the essential basis for personal development of the employee and therefore his family, even of the state's economy. However, the job security of workers in general has been increasingly restricted, either by various causes of political, economic, social, among others; this has led many workers to stay constantly in unemployment and an economic activity without allowing them the right to good living; and receiving compensation bonuses and insignificant either by eviction or wrongful dismissal, which in many cases do not even come to collect. In this situation, personally I disagree with the bonus established by eviction, because analyzing in reality this area the same it is ridiculous and does not constitute an economic benefit for the employee for their service, it is easy to see daily in the Labour Inspectorate, when workers who have completed an employment relationship out with small amount of money and do not reflect a true compensation for their service rendered to this is that in the private sector especially the salaries of workers are generally by the minimum set by law for that reason be a reform of the Labour Code regarding the termination of the employment agreement and Rewards.